(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
This study is the process of English curriculum development aims at analyzing the targets needs, learning needs, and the patterns of local wisdom insertion. This study was conducted through Focused Group Discussion (FGD), semi-structured interview, and content analsysis were used for 12 vocational school teachers and 2 officals of the state and private government institutions (The Department of Education and Culture, NTB Province & the Institute of ROWOT Nusantara Lombok). Necessity, the results of the target need analysis on local knowledge and language competence for developing skills and abilities, needs based, and contextual learning. Lacks, the gaps as the fundamental problems elicited from the current curriculum. Wants, the students’ desire to knowledge and vocational background-based curriculum contents. English learning design is associated with tourism competencies embedded with local wisdoms. The local wisdoms’ elements which can be developed into the English curriculum, that is, values of knowledge, social norms, and cultural acculturations, the marriage systems, patterns of family, and the other social cultural activities, and the elements of aesthetics. The patterns of insertion can be done through designing with paradigm of pedagogical orientation, insertion models, insertions in content of materials designed by developing the language skills, the use of teaching-learning methods with local insertions, developing student exercises-based insertions.